Pemanfaatan Hasil Data Digital Elevation Model untuk Estimasi Produksi Pertambangan Pasir dan Batu - Robiul Awaliah, Mesya Anggita; Marsisno, Waris (Seminar Nasional Official Statistics, 2024)
Sand and gravel (sirtu) are important materials in construction activities. Magelang Regency is a strategic area for sirtu mining with an abundant supply from Mount Merapi. Until now, data collection on sirtu mining still done manually through reporting from mining business owners. This research aims to estimate sirtu production data through the formation of Digital Elevation Model (DEM) data sourced from Sentinel-1 imagery using the Interferometric Synthetic Aperture Radar (InSAR) method. The DEM is processed using the cut and fill method to produce estimates of sirtu production. It is hoped that this research can be an alternative for collecting data on sirtu mining production in Magelang Regency. The research results show that the DEM obtained from Sentinel-1 imagery using the InSAR method has quite good quality so that the DEM can be used as a basis for calculating sirtu mining production estimates in Magelang Regency